A combination of immunohistochemical markers, MUC1, MUC5AC, PAX8 and growth pattern for characterization of mucinous neoplasm of the ovary. Issue 5 (19th February 2022) - Chelariu-Raicu, Anca; Holley, Eva; Mayr, Doris; Klauschen, Frederick; Wehweck, Fabienne; Rottmann, Miriam; Kessler, Mirjana; Kaltofen, Till; Czogalla, Bastian; Trillsch, Fabian; Mahner, Sven; Schmoeckel, Elisa
Abstract : Objective: Because mucinous carcinomas are rare tumors that affect several organ sites and are known to originate from different tissues, leading to frequent misdiagnoses, the objective was to characterize the differences between primary mucinous tumors of the ovary and metastatic mucinous cancer to the ovary by studying the expression pattern of several candidate biomarkers. Methods: Tissue samples of mucinous histology were obtained between 1985 and 2015. Individual ovary and colon tissue samples were analyzed, including standard (PAX8, CK20, CK7, CDX2, SATB2, estrogen/progesterone) and new (MUC1, MUC5AC) biomarkers, which were then scored for immunoreactivity semi-quantitatively. Results: The study cohort included 98 mucinous tumor samples, including benign mucinous cystadenoma (n=24), mucinous borderline tumors (n=24), mucinous carcinomas (n=40), and metastatic mucinous ovarian carcinomas (n=10). A strong positive correlation was found between PAX8 scoring (p=0.003), CK7 scoring (p=0.0001), and MUC1 scoring (p=0.001) in primary mucinous ovarian cancer. Tumors of increasing invasiveness were analyzed and a significant decrease in the scoring of MUC5AC (p=0.001) was observed, with a stronger expression in adenomas (87%) and borderline tumors (75%), and a lower expression in mucinous cancers (42%). Patients survived significantly longer when their tumors expressed high PAX8 and showed an expansile invasion pattern (p=0.005 and p=0.015, respectively) compared with patients with PAX8-negative tumors and destructive invasion pattern. Conclusion: The study data support the diagnostic value of MUC1 as a new biomarker to differentiate between primary and metastatic mucinous ovarian cancer. In addition, the tumor growth pattern along with the PAX8 immunophenotype might represent potential prognostic biomarkers for primary mucinous ovarian carcinomas.